Women Entrepreneurs in Developing Contexts: A Justification For Contextualised Research Through An Islamic Lens. - Adam, Amizahanum; Syed Yusuf2, Sharifah Norzehan; Puteh Salin, Ahmad Saiful Azlin; Zamri, Norhayati; Mohd Fatzel, Farah Husna (Journal of Islamic, Social, Economics and Development, 2025)
Women entrepreneurs have emerged as significant contributors to economic growth, reductions in poverty, and the resilience of communities, particularly in countries that are still in the process of modernisation. Despite this, a significant portion of the existing body of literature continues to be controlled by Western-centric paradigms that ignore the socio-cultural, religious, and institutional realities that women in non-Western settings are confronted with. This paper presents a conceptual rationale for the need to conduct localised research on women entrepreneurs. Drawing on the unique intersection of gender, social, and Islamic values within the Malaysian context, this paper calls for an inclusive research agenda that acknowledges the structural, cultural, and relational dimensions shaping women’s entrepreneurial sustainability.